(untitled) (Research, Society and Development, 2021)
The purpose of this ex vivo study was to evaluate the effectiveness of two irrigation techniques against E. Faecalis biofilm: conventional irrigation (CI) and passive ultrasonic irrigation (PUI). Furthermore, to investigate a possible cumulative effect of disinfection in the final irrigation, leaving the hypochlorite in the root canal for 2 or 5 minutes without agitation. A total of 63 premolars were divided into 9 groups (n = 7): Groups CI - 2.5 and CI - 5.25: Conventional irrigation with 2.5% and 5.25% NaOCl, respectively, a total of 6 mL for 1 min. Groups CI/PUI - 2.5 and CI/PUI - 5.25: CI + PUI with 2.5% and 5.25% NaOCl respectively, a total of 12 mL for 2 min. Groups CI/PUI - 2.5-2 (total of 14 mL for 4 min) and CI/PUI - 2.5-5 (total of 14 mL for 7 min): CI + PUI, plus final irrigation leaving the NaOCl 2,5% in the root canal for 2 or 5 minutes without agitation, respectively. Groups CI/PUI - 5,25-2 (total of 14 mL for 4 min) and CI/PUI - 5,25-5 (total of 14 mL for 7 minutes): CI + PUI, plus final irrigation leaving the NaOCl 5,25% in the root canal for 2 or 5 minutes without agitation, respectively. Control Group: CI + PUI, final irrigation leaving sterile saline solution for 5 min. The CI/PUI - 5,25 group showed a significantly greater reduction of E. faecalis than in the CI/PUI - 2.5 group. All other groups did not differ significantly from each other. The control group showed a less efficient reduction of E. faecalis. The CI associated with PUI was sufficiently able to reduce the bacterial load of E. faecalis. The final irrigation, leaving the hypochlorite in the root canal for 2 or 5 minutes without agitation did not demonstrate relevance in this study. Successive changes of the irrigating liquid, resulting in greater volume, demonstrated better results in disinfecting the root canal system.